Sistema solar fotovoltaico aislado para el suministro de energía eléctrica de una vivienda en la comunidad rural Mocochal, Calceta - Sacón Loor, María Yamileth (2023)
Ecuador, given its geographical conditions, is consolidated as one of the countries with the greatest energy potential for the use of renewable energies, highlighting solar photovoltaic, as an excellent alternative for isolated rural communities that do not have electrical service. The objective of the investigation was to evaluate the conditions of the location and the area of influence in the efficiency of the isolated photovoltaic system for the supply of electrical energy of a house in the Mocochal - Calceta community, for which a recognition of the place and the analysis of climatic information with data provided by the EMESPAM MFL; in addition, solar radiation maps were prepared. Subsequently, an analysis of sociodemographic information in the study area was carried out through a survey, the calculations of the photovoltaic design for the selected house were made and based on the bibliographic review the implemented panel was selected. Finally, the installation of the photovoltaic system and the monitoring for 32 days (28 days of March and 4 days of April) were carried out. The results obtained indicate that the radiation level of the place is high (4927 Wh/m2/day; T min 22.43°C; T max 31.62°C and 115.98 HSP); it was found that for an average energy consumption of 0.187 kWh/day, a 50W polycrystalline panel is required. The efficiency of the panel reached a value of 7.87% compared to 14.1% of the manufacturer. It is concluded that the isolated photovoltaic system reached 55.65% of the projected efficiency, accepting the idea to defend.